Positron plasma wakefield acceleration in a self-driven hollow channel - Amorim, L. D. (2021)
In this work we propose a novel positron driven plasma wakefield acceleration configuration in the non linear regime using tightly focused positron drive beams to create a hollow plasma channel with no background plasma ions, where positrons can accelerate to high energy. A simplified model for the background plasma ion motion in this scenario was analyzed. The proposed scheme was explored numerically resorting to multi-dimensional PIC simulations using the numerical code OSIRS.